A Cross-Sectional Survey of the Activity of Palliative Care Teams in Portugal. (November 2013) - Gonçalves, Ferraz; Almeida, Ana; Antunes, Catarina; Cardoso, Alice; Carvalho, Margarida; Claro, Maria; Coimbra, Francisca; Diniz, Inês; Fonseca, Bruno; Fradique, Emília; Gonçalves, Edna; Gonçalves, Florbela; et al.
Of the 21 Portuguese teams identified, 10 accepted to participate in the study. A total of 164 patients were included with a median of 15.5 per team (4-32). Of all the patients included, 60 (37%) were identified as inpatients in palliative care units; 59 (36%) by an intrahospital support team; 26 (16%) as outpatients; and 19 (12%) at home. The median age was 71 years (16-95). Fifty-one percent were females. The diagnosis was cancer in 151 (92%) patients. The most common cancer was colorectal in 22 (15%) patients, followed by gastric 17 (11%), head and neck 17 (11%), breast 15 (10%), and lung cancers 14 (9%). All patients were treated by doctors and nurses experienced in palliative care.